The Effectivity of Peer Education Module on Knowledge, Attitude, and Fast Food Consumption in Adolescents - Saskiyanto Manggabarani; Irfan Said; Anto J. Hadi; Rapida Saragih; Muhammad Cristandy; Neni Ekowati Januariana (Journal of Health Promotion and Behavior, 2020)
Background: Increasing obesity sufferers every year, in a few decades becomes an important problem. Increased obesity can lead to an increased risk of degenerative diseases which can cause death. Several attempts have been made to prevent and treat obesity. The purpose of this study is to determine the effectiveness of peer education on knowledge, attitudes, and consumption of fast food in adolescents.Subjects and Method: This study is a randomized controlled trial conducted at a Junior High School (SMP Negeri 6 Medan), North Sumatera. Samples taken were 60 students chosen randomly. The sample was divided into 2 groups: a peer game education leaflet group and a peer education module group. The dependent variable is knowledge, attitudes, and habits of fast food consumption. The independent variable is the provision of leaflets and peer education modules. The data were obtained through interview, Food Frequency Questionnaire (FFQ), and Food Recall 24 hours. Data were analyzed using t-test.Results: The results showed that the value of nutritional knowledge and obesity in the control group (Mean= 12.07; SD= 1.44) was lower compared to the intervention group (Mean= 13.50; SD= 1.99), but not statistically significant (p= 0.523). Attitudes toward nutrition and obesity in the control group (Mean= 11.50; SD= 1.22) were lower than those in the intervention group (Mean = 13.00; SD= 1.78) and were statistically proven significant (p= 0.008). The score of fast food consumption habits in the control group (Mean= 8.17; SD= 1.23) is lower than that of the intervention group (Mean= 9.50; SD= 1.17) and is statistically proven significant (p <0.001).Conclusion: The nutrition peer education module has been shown to be effective in increasing attitudes about nutrition and obesity and reducing fast food consumption habits and this has been statistically significant. The nutrition peer education module increases knowledge scores, but is not statistically significant.Keywords: obesity, consumption of fast food, peer educationCorrespondence: Saskiyanto Manggabarani, Helvetia Health Institute, Jl. Kapten Sumarsono No. 107 Medan, North Sumatera, Indonesia. Email: zhakymanggabarani@gmail.com.Journal of Health Promotion and Behavior (2020), 5(1): 35-42https://doi.org/10.26911/thejhpb.2020.05.01.05